High-frequency modulated secondary-side self-powered isolated gate driver for full range PWM operation of SiC power MOSFETs - Garcia, Jorge; Gurpinar, Emre; Castellazzi, Alberto (2017)
The present work proposes a solution for an isolated gate driver suitable for SiC MOSFETs. The driver is implemented by means of two small magnetic transformers, to provide the turn-on and turn-off gate signals, as well as the power required for an adequate gate control. The operation is based on the modulation of the PWM pulses with a high frequency (HF) square-waveform signal. The resulting modulated AC waveform is applied to the primary side of the first transformer, and reconstructed at the secondary side to obtain the gate driving signal. Simultaneously, the HF modulating signal is connected to the primary of the second transformer, to provide the required gate drive voltage levels and power at the secondary side, ensuring full range duty ratio operation. Given that both primary side signals are HF symmetrical waveforms, saturation is avoided at both transformers, for any duty ratio operation. Therefore, the proposed solution provides galvanic isolation for power and gate signal transfer with very small core sizes, allowing for an overall size reduction vs. conventional solutions. This enables much more compact designs, which are critical in high-power density applications and multilevel converters. After describing the basic operation, experimental results on a prototype are shown, thus demonstrating the feasibility of the proposed solution